Revision of the Oriental leafhopper genus Parallygus Melichar (Hemiptera: Cicadellidae: Deltocephalinae) with description of new species - Dai, Wu; Viraktamath, C. A.; Webb, M. D.; Zhang, Yalin (Zootaxa, 2012)
The Oriental leafhopper genus Parallygus Melichar is revised and redescribed based on study of its type species, P. divar-icatus Melichar, from Sri Lanka. Based on its paired aedeagal shafts, a feature of some other tribes, it is only tentativelyretained in Athysanini. Three new species, Parallygus burmindicus Viraktamath & Webb, sp. nov. (India: West Bengal,Meghalya; Myanmar: Mishmi Hills), P. jiuhuaensis Dai & Zhang, sp. nov. (China: Anhui) and P. rameshi Viraktamath &Webb, sp. nov. (India: West Bengal) are described and illustrated together with P. divaricatus Melichar and Parallygusguttatus Matsumura comb. reinstated described from Taiwan. The latter species is reinstated into its original genus Pa-rallygus from Phlepsius and is also recorded from mainland China and India (new records). A key to species is also provided.